Treatment of Fuchs Endothelial Dystrophy by Descemet Stripping Without Endothelial Keratoplasty. Issue 10 (October 2016) - Borkar, Durga S.; Veldman, Peter; Colby, Kathryn A.
Abstract : Purpose: To evaluate the effect of deliberate removal of the central Descemet membrane on endothelial function and morphology in patients with Fuchs endothelial dystrophy (FED) and cataract undergoing phacoemulsification. Methods: In this retrospective case series, patients with FED and visually significant cataract underwent phacoemulsification in an academic cornea practice in Boston, MA. Four millimeters of the central Descemet membrane was stripped and removed after intraocular lens insertion. Vision, corneal pachymetry, and confocal imaging of the endothelial anatomy were performed before surgery and at 1, 3, 6, and 12 months after surgery. Patients were classified as fast responders, responders, slow responders, and nonresponders on the basis of postoperative time to resolution of corneal edema with visible central endothelial mosaic. Results: Eleven patients (13 eyes) aged 51 to 91 years were included in the study. No eyes had countable central endothelial cells by confocal imaging before surgery. Preoperative visual acuity ranged from 20/25 to 20/400. All corneas showed stromal and microcystic edema in the area of Descemet stripping at days 1 and 7 after surgery. Four eyes demonstrated resolution of corneal edema with visible central endothelial cell mosaic (range: 410–864 cells/mm 2 ) by postoperative month 1 with visual acuity ranging between 20/25 and 20/40. Four additional eyes demonstrated a similar response by postoperative month 3 and an additional 2 eyes had resolution of corneal edema with an intact central endothelial mosaic at postoperative month 6 or later. Cell counts (range: 428–864 cells/mm 2 ) were maintained in all 10 responders at the last follow-up visit (range: postoperative months 6–24). Final vision ranged from 20/15 to 20/20 in these 10 eyes with the exception of 2 eyes with retinal pathology. Three eyes required endothelial keratoplasty. Conclusions: Repopulation of the central corneal endothelium with corneal deturgescence can occur after deliberate central Descemet stripping in patients with FED who underwent cataract removal. This may offer a novel treatment for patients with FED that could reduce the need for endothelial transplantation. Further studies are needed to delineate the optimal patient population for Descemet stripping because not all patients will respond to this intervention.